Two-Function Computer Functions in the use of Information Modeling Based on Imitations - Kahramonova Khumora Kahramanovna (Genius Journals, 2022)
In this article, in the use of modeling of information-based information, the views of the information and vocabularization based on the educational capacity and educational and educational training, which are determined by educational and educational standards, covered
Keywords: Immitation; Modeling; Dominant Function; An official performer